PEMANFAATAN HIJAUAN RAWA SEBAGAI PAKAN TERNAK PADA KELOMPOK TERNAK BANUA RAYA - Tintin Rostini; Achmad Jaelani (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
Forage is the primary food source for ruminant livestock . The availability of forage not comparable wit population livestock. Purpose of husband devotion is to review enhance knowledge Farmers / ranchers hearts knowledge introduction to forage feed swamp land and preservation process and can provide livestock fodder season throughout quality good nutrition . Which method do is counseling , which was held on Livestock Banua Raya,, district Bati - bati , Tanah Laut regency . It was concluded that the feed is a cover charge that paled big hearts cattle fattening business. To service activities ' husband society able to provide motivation for a review to increase farmer profits